Role of leadership styles in escalating the employee productivity: moderating role of knowledge sharing - Mansi Alshammari, Waleed; Abbas Ali, Dhakir (Edelweiss Applied Science and Technology, 2024)
In the dynamic world, the experience of all kind of professionals is changing; the central role of leadership and transfer the exclusive knowledge among the works has become essential concept. Leaders develop such environment that develops the sense of sharing and collaboration within the organization. The study has set the target to investigate the role of leadership styles (inclusive leadership and authentic leadership) in increase the productivity of employee, to investigation the moderating role of knowledge sharing between leadership styles and employee productivity in the context of Hail health cluster, to find out the theoretical foundation of study. Data is collected with the help of questionnaire developed on the base precious studies. The data of 253 participants were collected from the hospitals of Hail cluster. Further, data is analyzed by using the PLS-SEM. The finding of this study elaborates that authentic leadership has positive and significant relationship with productivity of employee in healthcare center. The result also fount hat inclusive leadership also play important role in enhancing the employee productivity. The knowledge sharing appears as important moderator which performance efficient role to facility the employee with knowledge from leaders. This study has empirical, theoretical and practical contribution in multiple ways. This study expends the understanding of leadership styles with productivity of employees by emphasizing on its dimension authentic leadership and inclusive leadership, instead of merely focusing on general concept of leadership. This study highlights the importance of knowledge sharing in the healthcare sector along with the collaborations of leaders for learning as well as productivity.